BAYESIAN APPROACH: AN ALTERNATIVE TO THE ADDITIVE MAIN EFFECT AND MULTIPLICATIVE INTERACTION MODELS FOR GENOTYPES THROUGH ENVIRONMENTAL INTERACTIONS (Nativa, 2024)
Genotypes of different genetic structures behave differently in various environmental conditions. Genotype-by-environment interaction (GEI) is referred to as differential responses of different genotypes across different environments; GEI is of great importance because of the higher performance of genotypes that GEI assesses. However, the presence of GEI makes analysis more complicated. To up-root these assessment complications, several methods have been proposed, such as Principal Component Analysis (PCA), Cluster Analysis, Additive Main effects, Multiplicative Interaction (AMMI) models, and Genotype plus Genotype by Environment interaction (GGE). These methods neither overcome the problem of over-parameterization nor use the prior information. This study aims to use a technique to address these problems; for this purpose, wheat crop data comprised of 30 genotypes tested across 13 different locations of Punjab, Pakistan, for two consecutive years was used. The layout of the experiment was a Randomized Complete Block Design (RCBD). In this study, a comparison was made between Classical methods AMMI, GGE biplot, and Bayesian approach using Von-Mises Fisher distribution as prior. Classical methods showed that genotype V-11098 was the most desirable based on stability and high-yield performance. The Bayesian approach was used for GEI because it simplifies statistical interpretation by relaxing some constraints. It uses the prior information and provides solutions using the Markov Chain Monte Carlo (MCMC) algorithm. Bayesian strategy for analysis of GEI was used to assess the general, specific performance of genotypes and risk related to genotype. Analysis revealed that bi-linear terms  for genotype NS-10 genotype and  for environment S13 (Piplan-14) were found significant, indicating that these affect interaction. It was observed that the Bayesian approach could nicely explore GE interaction.Keywords: Genotype-by-environment interaction (GEI); Von Mises-Fisher Distribution; Markov Chain Monte Carlo (MCMC). Abordagem bayesiana: uma alternativa aos modelos de efeito principal aditivo e interação multiplicativa para genótipos por meio de interações ambientais RESUMO: Genótipos de diferentes estruturas genéticas apresentam comportamentos distintos em várias condições ambientais. A interação genótipo-por-ambiente (GEI) é referida como respostas diferenciais de diferentes genótipos em diferentes ambientes; a GEI é de grande importância devido para  definição do maior desempenho dos genótipos que a GEI avalia. No entanto, a presença da GEI torna a análise mais complicada. Para erradicar essas complicações de avaliação, vários métodos foram propostos, como Análise de Componentes Principais (PCA), Análise de Cluster, Efeitos Principais Aditivos, modelos de Interação Multiplicativa (AMMI) e Genótipo mais interação Genótipo por Ambiente (GGE). Esses métodos não superam o problema da superparametrização nem usam as informações anteriores. Este estudo visa usar uma técnica para abordar esses problemas; para esse propósito, foram usados ​​dados de safra de trigo compostos por 30 genótipos testados em 13 locais diferentes de Punjab, Paquistão, por dois anos consecutivos. O layout do experimento foi um Delineamento de Blocos Completos Randomizados (RCBD). Neste estudo, foi feita uma comparação entre os métodos clássicos AMMI, GGE biplot e abordagem Bayesiana usando a distribuição de Von-Mises Fisher como prior. Os métodos clássicos mostraram que o genótipo V-11098 foi o mais desejável com base na estabilidade e no desempenho de alto rendimento. A abordagem Bayesiana foi usada para GEI porque simplifica a interpretação estatística ao relaxar algumas restrições. Ela usa as informações anteriores e fornece soluções usando o algoritmo Markov Chain Monte Carlo (MCMC). A estratégia Bayesiana para análise de GEI foi usada para avaliar o desempenho geral e específico dos genótipos e o risco relacionado ao genótipo. A análise revelou que os termos bilineares μ_25,1 para o genótipo NS-10 e ν_13,1 para o ambiente S13 (Piplan-14) foram considerados significativos, indicando que afetam a interação. Foi observado que a abordagem Bayesiana poderia explorar bem a interação GE.Palavras-chave: interação genótipo-por-ambiente (GEI); distribuição de Von Mises-Fisher; cadeia de Markov Monte Carlo (MCMC).